Dusun custom in Putatan District - Osman bin Orang Kaya Kaya Pangeran Haji Omar Pangeran 1884-; Woolley, G. C. (George Cathcart) 1876-1947 (Kota Kinabalu Natural History Publications (Borneo), 2006)
Compilation of Dusun adat and customary laws in Putatan, Sabah.
Includes bibliographical references.
In English, and some texts of original laws in Malay.
Keywords: Law, Dusun; Adat law -- Malaysia -- Sabah